Cancer stem cells - Rajasekhar, Vinagolu K. (Hoboken, New Jersey : John Wiley & Sons, 2014)
"Cancer Stem Cells covers a wide range of topics in cancer stem cell biology, including the functional characteristics of cancer stem cells and how they're generated, where they are localized, the means by which cancer stem cells can be targeted, and how cancer stem cells can be reprogrammed back to normal tissue stem cells. Each chapter begins with a brief historical note and concept summary, followed by a description of the latest basic or clinical advance associated with the topic.Cancer Stem Cells builds systematically from coverage of the basic research stage to an advanced research level, from clinical relevance to therapeutic potential, and will be a valuable resource for professionals in the fields of cancer research and stem cell biology"--Provided by publisher.
Oxytocin and vasopressin systems: oxytocin, vasopressin, and their interplay with gonadal steroids: essentials of cancer stem cells and conceptual modeling -- Theoretical and experimental foundations of the "cancer stem cell" model -- The hallmarks of prostate cancer stem cells -- Self-renewal, induced proliferation, and autonomous cell growth represent distinct modes of cell multiplication: relevance to the cancer stem cell theory -- Human embryonic stem cells and cancer: modeling disease in a dish -- Cancer stem cell as a result of a reprogramming-like mechanism: implications in tumor development and treatment -- A cancer stem cell model: an insight into the conversion of induced pluripotent stem cells to cancer stem-like cells -- Altruistic stem cells and cancer stem cells -- The emerging concept of EMT-induced cancer stem cells -- Models to study chronic myeloid leukemia cancer stem cells -- Cancer stem cells in melanoma: biomarkers and mathematical models -- Stem cells in liquid tumors -- Acute myeloid leukemia stem cells: updates and controversies -- Leukemia-initiating cells in acute lymphoblastic leukemia -- Stem cells in solid tumors -- Lung cancer stem cells and resistance to radiotherapy -- Prostate cancer cell heterogeneity and prostate cancer stem cells -- Glioblastoma stem cells drive tumor recurrence and patient relapse: what's the evidence? -- Stem cells and pancreatic cancer -- Melanoma subpopulations with cancer stem cell phenotypes -- Sarcoma stem cells -- Cancer stem cells in tumor metastasis perspective -- Cancer stem cells in metastasis and minimal residual disease -- Role of cancer stem cells in metastasis -- Cancer stem cells and the stromal microenvironment -- A perspective on breast cancer malignant progression: from cancer stem cell intra tumor heterogeneity to metastasis-initiating cells -- Novel and potential targets in cancer stem cells -- Targeting cancer stem cells: modulating embryonic stem cell signaling, epigenetics, and tumor metabolism -- Oct4, Oct1, and cancer stem cells -- The role of Cripto-1 in cancer and cancer stem cells -- Leptin signaling in the regulation of stem and cancer stem cells -- Tumor-initiating stem-like cells: carcinogenesis through toll-like receptors, environmental factors, and virus -- The role of epithelial cell polarity pathways on cancer stem cells -- Cancer-initiating cells, exosomes, and the premetastatic niche -- Microrna therapeutics to target brain tumor stem cells -- The riboproteome orchestrates self-renewal and cell fate in leukemia -- Clinical relevance of cancer stem cells in patients -- Targeting different states of breast cancer stem cells -- Difficulties in targeting the beating heart: therapeutic implications of the cancer stem cell hypothesis in melanoma -- Targeting cancer stem cells for overcoming drug resistance and cancer progression -- The role of cancer stem cells in tumor radioresistance.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Neoplastic Stem Cells; Stem cells; Cancer; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Cancer; Stem cells; Krebs; Stammzelle; Neoplastic Stem Cells; Electronic books; Electronic books